2017
DOI: 10.1002/jso.24870
|View full text |Cite
|
Sign up to set email alerts
|

Effective excision of cutaneous squamous cell carcinoma of the face using analysis of intra‐operative frozen sections from the whole specimen

Abstract: Surgical excision with WIFSA is an excellent treatment modality for cSCC of the face because of its accurate method for assessment of complete tumor removal, low recurrence and metastasis rate, short average duration of treatment, and low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Hutting et al and Kedilioglu et al have previously determined the accuracy of the WIFSA technique. Hutting et al and Kedilioglu et al each found a total agreement of 98.8% . In this study, we calculated a total accuracy of 98.4%, which confirms these earlier reports.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hutting et al and Kedilioglu et al have previously determined the accuracy of the WIFSA technique. Hutting et al and Kedilioglu et al each found a total agreement of 98.8% . In this study, we calculated a total accuracy of 98.4%, which confirms these earlier reports.…”
Section: Discussionsupporting
confidence: 92%
“…As well as accurate, WIFSA has been proven to be a fast technique for analyzing the excision margins . We emphasize this by demonstrating that on average, for radical removal of the tumor, 1.4 excisions were needed.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Die Breite der histologischen Brotlaibschnitte im Rahmen der WLE wird in der gesamten vorliegenden Literatur nur zweimal angegeben: 1–4 Querschnitte bei medianem Tumordurchmesser von 17 mm von 120 PEK und 1–3 mm breite Streifen bei Tumordurchmesser < 20 mm in 83 % von 160 PEK . Die Definition für R0 oder randbildend R1 ist in den hierzu gefundenen Publikationen nicht einheitlich.…”
Section: Ergebnisseunclassified